Translanguaging space and creative activity: theorising collaborative arts-based learning. (2nd January 2018) - Bradley, Jessica; Moore, Emilee; Simpson, James; Atkinson, Louise
ABSTRACT: This paper focuses on an innovative transdisciplinary educational arts-based learning project, LangScape Curators, which links to and leads from research conducted for the AHRC-funded 'Translation and Translanguaging' project. Here, we describe how we work collaboratively with creative practitioners to use a variety of creative arts methods with young people to explore the linguistic landscapes of Leeds. We propose a theoretical framework for collaborative research activity of this nature, and we use one of the creative arts activities – collage – to exemplify visual understandings of how communicative repertoires and linguistic landscapes are explored through co-produced pedagogical workshops. The programme and its associated research make an original contribution to linguistic landscape-based collaborative ethnographic research. We conclude by setting out directions for the future of these activities and their application in applied linguistics research and practice.